How Preparedness Can Work for Busy Utilities. Issue 8 (1st August 2013) - Spence, Shannon; Warren, Linda P.
Abstract : Staff from hundreds of utilities have spoken with me about preparedness, and every one of them has a story to share. Sometimes it was an accident that caused a chlorine leak, or a well‐meaning citizen walking into city hall with an unexploded ordinance from the Civil War, or a cyber‐system shut‐down because of an e‐mail virus. Every water and wastewater system is vulnerable in some way; it is the responsibility of each system's leadership to be prepared just in case the unthinkable occurs. If you are reading this, you likely have an interest in emergency preparedness, and chances are your plate is overflowing, as is the list of items on which to spend your budget. That's why this month's column is about what a busy utility can do to increase its preparedness.